Konsep Maqāmāt wa Aḥwāl dalam Pemikiran al-Ghazālī dan Relevansinya bagi Pembinaan Moral Modern - Cici Nurmianty; Indo Santalia (STKIP Subang, 2026)
The phenomenon of moral degradation, identity crisis, and increasing psychological stress in the modern era demonstrates the need for a spiritual approach capable of guiding individuals toward inner stability and ethical character. Sufism, as proposed by al-Ghazālī, provides the concepts of maqāmāt (spiritual stages) and aḥwāl (inner states) as an integral framework for purifying the soul. This study aims to elaborate on the concepts of maqāmāt and aḥwāl according to al-Ghazālī and analyze their relevance in modern moral development. The method used is a literature study. The results show that maqāmāt is a spiritual endeavor achieved through self-discipline, while aḥwāl is a divine gift given as a result of the maturity of maqām. The integration of the two produces a spiritual personality that is moral and emotionally stable. This concept has proven relevant for modern moral development, especially in the context of character education, mental health, and the search for the meaning of life